Perturbative breaking of the pseudospin symmetry in the relativistic harmonic oscillator - Lisboa, R.; Malheiro, M.; de Castro, A. S.; Alberto, P.; Fiolhais, M. (World Scientific Publ Co Pte Ltd, 2004)
We show that relativistic mean fields theories with scalar S, and vector V, quadratic radial potentials can generate a harmonic oscillator with exact pseudospin symmetry and positive energy bound states when S = -V. The eigenenergies are quite different from those of the non-relativistic harmonic oscillator. We also discuss a mechanism for perturbatively breaking this, symmetry by introducing a tensor potential. Our results shed light into the intrinsic relativistic nature of the pseudospin symmetry, which might be important in high density systems such as neutron stars.
Keywords: pseudospin symmetry; harmonic oscillator; tensor potential